Validity and Responsiveness of a Modified Balance Error Scoring System Assessment Using a Mobile Device Application in Patients Recovering from Ankle Sprain - Michael S Crowell; Eliot Thomasma; Erin Florkiewicz; Richard Brindle; Megan Roach; Donald Goss; Will Pitt (International Journal of Sports Physical Therapy)
# Background